Clinical evaluation of 107 anterior teeth restored with direct nanofilled resin composite: Up to 32 months - Toz Akalın, Tuğba; Kuşdemir, Mahmut; Gözükara Bağ, Harika; Özcan, Mutlu (My University, 2016)
Aim: This study evaluated the clinical performance of a nanofill resin composite in Class III and IV cavities.Materials and Methods: One hundred and seven Class III and Class IV restorations were performed with a nanofill resin composite. Restorations were evaluated using the modified USPHS/FDI criteria. The changes were analyzed using McNemar and Marginal Homogeneity and Kaplan-Meier tests.Results: Fourteen absolute failures were encountered resulting in a survival rate of 86.8% (Kaplan-Meier). Nanofill resin composite showed acceptable clinical performance up to 32 months of service.Conclusion: However color stability and retention decreased at the end of two year fol-low up instead of fractures.

Amaç: Bu çalışmanın amacı, nanofil bir rezin kompozitin klinik performansının sınıf 3 ve sınıf 4 kavitelere yapılan restorasyonlar ile değerlendirilmesidir.Gereç ve Yöntem: 107 adet sınıf 3 ve sınıf 4 restorasyon nanofil rezin kompozit ile re-store edildi ve daha sonra modifiye USPHS/FDI kriterleri ile değerlendirildi. Sonuçlar McNemar ve Marjinal Homojenite ve Kaplan-Meier testleri ile analiz edildi.Bulgular: 14 adet restorasyonda başarısızlık tespitiyle birlikte %86,8 lik bir restorasyon başarı oranı yakalandı. Nanofil rezin kompozitin 32 aylık periyotta kabul edilebilir bir klin-ik başarı gösterdiği tespit edildi.Sonuç: 2 yıllık takip sonunda renk stabilitesi ve retansiyonun azaldığı belirlendi.
Nanofil rezin kompozitlerle restore edilmiş 107 anterior dişin klinik olarak değerlendirilmesi: 32 aylık takip
Keywords: Adhesion; Class III Cavities; Nanofilled Composite; Resin; Adezyon; Class III Kaviteler; Nanofil Kompozit; Rezin